Performance and Feasibility Analysis of a Grid Interactive Large Scale Wind/PV Hybrid System based on Smart Grid Methodology Case Study South Part – Jordan - Qais H. Alsafasfeh (Center of Biomass & Renewable Energy (CBIORE), 2015)
Most recent research on renewable energy resources main one goal to make Jordan less dependent on imported energy with locally developed and produced solar power, this paper discussed the efficient system of Wind/ PV Hybrid System to be than main power sources for south part of Jordan, the proposed hybrid system design based on Smart Grid Methodology, the solar energy will be installed on top roof of electricity subscribers across the Governorate of Maan, Tafila, Karak and Aqaba and the wind energy will set in one site by this way the capital cost for project will be reduced also the simulation result show the feasibility is a very competitive and feasible cost . Economics analysis of a proposed renewable energy system was made using HOMER simulation and evaluation was completed with the cost per kilowatt of EDCO company, the net present cost is 2,551,676,416, the cost of energy is 0.07kWhr with a renewable fraction of 86.6 %.